SELF- COMPASSION DAN RESILIENSI PADA MAHASISWA MEMILIKI KELUARGA TIDAK HARMONIS - Kholifatun Nikmah; Yuarini Wahyu Pertiwi (ADISAM PUBLISHER, 2023)
The purpose of this study is to find out whether there is a relationship of self-compassion with reselience in students of disharmonious families at Bhayangkara University In Greater Jakarta. This type of research is a quantitatively correlated descriptive type. The sample used as many as 142 students using purposive techniques. The results of the study basedon Spearman's rho correlation test showed self-compassion with resilience has a very high strength association. The plus in the correlation coefficient indicates a positive relationship between self- compassion and resilience in students of disharmonious families at BhayangkaraUniversity in Greater Jakarta (value r = 0.820** with p < 0.000). So it can be concluded thatself-compassion correlates with resilience in students of disharmonious families.